Analysis of competition and dominance level on the passenger car market of Republic of Korea - O. V. Kudryavtseva; P. S. Abramova; N. I. Markov (Мир новой экономики, 2023)
The article is devoted to the analysis of statistical data provided by the Committee of Automakers of the Association of European Businesses (AEB) on the volume of sales of passenger cars of various brands on the market of the Republic of Korea from 2010 to 2021. The article describes the history and current trends of the market in question. Moreover, the authors summarize previously conducted research on this topic, providing a list of relevant studies. By using the competitive analysis tool — SV matrix, the study aims to provide information of scientific importance on the subject of competitive environment within the market under consideration, as well as to identify leading companies. An interpretation based on the results of the study is presented as well. It includes an explanation of the dynamics in the market, including changes in the market share of companies within the selected time period, a description of the specificities of the modern market leaders development and the reasons for the existing competitive environment. The conclusion is made about the relative stability of the South Korean automobile market, which has a national manufacturer and retailer as a market leader throughout the analyzed period. Moreover, quite a reasonable assumption is made about the relevance of the development pattern of the South Korean automobile market for the corresponding market of the Russian Federation.